The Evidence Act, 1872 (Act No. 1 of 1872) with commentary - Iqbal, M.; Zahirul Huq, Al-Haj. (Lahore : All Pakistan Legal Decisions, 1968)
With up-to-date amendments and case law.
Includes index.
Keywords: Evidence (Law) -- Pakistan